2018
DOI: 10.1038/nchem.2907
|View full text |Cite
|
Sign up to set email alerts
|

Labelling and determination of the energy in reactive intermediates in solution enabled by energy-dependent reaction selectivity

Abstract: Any long-lived chemical structure in solution is subject to statistical energy equilibration, so the history of any specific structure does not affect its subsequent reactions. This is not true for very short-lived intermediates, since energy equilibration takes time. Here, this idea is applied to achieve the energy labeling of a reactive intermediate. The selectivity of the ring-opening α-cleavage reaction of 1-methylcyclobutoxy radical is found here to vary broadly depending on how the radical was formed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…We note that previous studies have demonstrated that the redistribution of excess vibrational kinetic energy among real modes has an impact on the selectivity of nonequilibrium processes. 40,41,42 In contrast to existing methods based on the analysis of real vibrational modes, the presented RMCF analysis is unique in its dissection of the imaginary reactive mode, translating the distribution of kinetic energy within this mode into a predictor of selectivity in complex reactions.…”
Section: And a General Prescription For Such A Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that previous studies have demonstrated that the redistribution of excess vibrational kinetic energy among real modes has an impact on the selectivity of nonequilibrium processes. 40,41,42 In contrast to existing methods based on the analysis of real vibrational modes, the presented RMCF analysis is unique in its dissection of the imaginary reactive mode, translating the distribution of kinetic energy within this mode into a predictor of selectivity in complex reactions.…”
Section: And a General Prescription For Such A Selectionmentioning
confidence: 99%
“…An important remark is that Goodman's 4-point approach was tested on reactions calculated with different methods, some of them selected by the original authors to maximize the agreement with experiments. 28,29,40 Under such conditions, both Goodman's and RMCF methods perform even better (Figures S4 -S5), yet this heterogeneity precludes the selection of a generally reliable method. For the same set of reactions, we herein show that with qualitatively correct selectivity in 93% (40 out of 43) and with the correct quantification (with a tolerance of 20%) in 71% of cases, the RMCF analysis with the B3LYP functional proves to be a general and balanced prescription requiring a single point from the PES complemented by qualitative information of the suspected products or chemical knowledge from the user.…”
Section: Comparison Of Rmcf With Existing Approaches Designed For Product Ratio Evaluationmentioning
confidence: 99%
“…This is not unusual and in fact common to any intermediate or product derived from a high in energy transition state (TS). 24 This excess energy originates from potential energy that is in part transformed into vibrational energy right after the intermediate or product formation (Scheme 2A). Because energy redistribution via intramolecular and intermolecular processes is extremely fast in solution, 25 excess vibrational energy does typically not affect subsequent reactions of an intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…At this timescale, the reactivity of the intermediate can compete with its excess energy redistribution and thermal equilibration. 24 For reactive intermediates with very short lifetimes, non-statistic distribution of energy can affect their dynamic behavior and thus control the reactivity of these species (Scheme 2B). Changes in reactivity can for example take place via selective vibrational activation of one part of a molecule or by specific vibrations with a displacement (momentum) that correlates with the geometry of a subsequent transition state and its displacement vector corresponding to the imaginary frequency (dynamic match).…”
Section: Introductionmentioning
confidence: 99%
“…Although many computational studies on the mechanism of DA and 1,3-dipolar cycloaddition reactions have been reported 3,4,6,[21][22][23][24][25][26] , computational works on the mechanism of HDA reactions are quite limited [27][28][29] . In addition, Carpenter, Hase, Houk, Singleton, Tantillo, and other groups carried out quasi-classical molecular dynamics (e.g., MD with a density-functional theory (DFT) method) studies to provide several new mechanistic concepts for several uncatalyzed DA reactions and other (almost metal-free) organic and enzymatic reactions (e.g., dynamically concerted and dynamically stepwise mechanisms, energy-dependent reaction selectivity, and dynamically controlled selectivity) [30][31][32][33][34][35][36][37][38][39][40][41][42][43] . These DFT MD studies offered us time-resolved mechanistic insights and helped elucidate the timing of the bond formation in (bio)chemical reactions.…”
mentioning
confidence: 99%